Achieving remarkable mechanochromism and white-light emission with thermally activated delayed fluorescence through the molecular heredity principle. Issue 3 (11th January 2016) - Xu, Bingjia; Mu, Yingxiao; Mao, Zhu; Xie, Zongliang; Wu, Haozhong; Zhang, Yi; Jin, Chongjun; Chi, Zhenguo; Liu, Siwei; Xu, Jiarui; Wu, Yuan-Chun; Lu, Po-Yen; et al.
Abstract : An asymmetric molecule created by molecular heredity exhibits remarkable mechanochromism and white-light emission. Abstract : Achieving high contrast mechanochromism (Δ λ em, max > 100 nm) and white-light emission under mild conditions from a single compound with a simple structure is a great challenge. Herein, we report a novel dual-emissive compound, namely SCP, with an asymmetric molecular structure that fully inherits the photophysical properties of the parent molecules SC2 and SP2 . SCP shows high contrast, linearly tunable mechanochromism and bright white-light emission arising from a combination of traditional fluorescence and thermally activated delayed fluorescence (TADF). The origin of the dual-emission for SCP was demonstrated based on the analysis of the white-emitting single crystals. In addition, a mechanism of luminochromism for SCP driven by the application of mechanical force is proposed. These observations present a rational design strategy for the development of high performance multi-functional materials for white-light emission.